(untitled) (Canadian Medical Education Journal, 2016)
Background: Global health electives offer medical trainees the opportunity to broaden their clinical horizons. Canadian universities have been encouraged by regulatory bodies to offer institutional support to medical students going abroad; however, the extent to which such support is available to residents has not been extensively studied. Methods: We conducted a survey study of Canadian universities examining the institutional support available to post-graduate medical trainees before, during, and after global health electives. Results: Responses were received from 8 of 17 (47%) Canadian institutions. Results show that trainees are being sent to diverse locations around the world with more support than recommended by post-graduate regulatory bodies. However, we found that the content of the support infrastructure varies amongst universities and that certain components—pre-departure training, best practices, risk management, and post-return debriefing—could be more thoroughly addressed. Conclusion: Canadian universities are encouraged to continue to send their trainees on global health electives. To address the gaps in infrastructure reported in this study, the authors suggest the development of comprehensive standardized guidelines by post-graduate regulatory/advocacy bodies to better ensure patient and participant safety. We also encourage the centralization of infrastructure management to the universities’ global health departments to aid in resource management.